2022
DOI: 10.1002/mame.202100801
|View full text |Cite
|
Sign up to set email alerts
|

High‐Sensitivity, Long‐Durability, and Wearable Pressure Sensor Based on the Polypyrrole/Reduced Graphene Oxide/(Fabric–Sponge–Fabric) for Human Motion Monitoring

Abstract: Fabrics are among the best ideal materials for fabricating low‐cost flexible pressure sensors due to their outstanding air permeability, flexibility, and micro/nanorough structure. However, most of the fabric‐based pressure sensors suffer from poor stability, which severely limits their applications in the real life. In the previous work, the pressure sensor assembled from polyester fabric and polyurethane sponge in an integrated design shows good stability. Herein, a novel type of wearable pressure sensors wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…For instance, Shu et al [13] developed iShoe, a pair of shoes that can map foot pressure anytime and anywhere, and the system has been successfully tested in local hospitals in Hong Kong for the prognosis of diabetic foot syndrome. Cheng et al [116] reported a piezoresistive pressure sensor based on PPy/rG /FSF (nylon fabric-latex foam-nylon fabric (FSF), reduced graphene oxide (rG ), and in situ molded polypyrrole (PPy)) composite for Parkinson's disease detection by monitoring the time of head lift and elevation. However, pressure sensors can also be applied to smart homes.…”
Section: Flexible Strain and Pressure Sensorsmentioning
confidence: 99%
“…For instance, Shu et al [13] developed iShoe, a pair of shoes that can map foot pressure anytime and anywhere, and the system has been successfully tested in local hospitals in Hong Kong for the prognosis of diabetic foot syndrome. Cheng et al [116] reported a piezoresistive pressure sensor based on PPy/rG /FSF (nylon fabric-latex foam-nylon fabric (FSF), reduced graphene oxide (rG ), and in situ molded polypyrrole (PPy)) composite for Parkinson's disease detection by monitoring the time of head lift and elevation. However, pressure sensors can also be applied to smart homes.…”
Section: Flexible Strain and Pressure Sensorsmentioning
confidence: 99%
“…The system consists of an amplifying/filtering circuit, a multichannel switch, an analog-to-digital converter (ADC) module, an microcontroller unit (MCU) processor, a Bluetooth module, and a host computer. After the host computer receives the signal through Polydimethylsiloxane (PDMS)/Ag 0.636 kPa À1 (0-1 kPa) 0.106 kPa À1 (1-60 kPa) 0.0135 kPa À1 (60-500 kPa) 0-500 kPa 6000 (10 kPa) [37] PDMS/Ag 1.005 kPa À1 (0-1 kPa) 0.625 kPa À1 (1-100 kPa) 0.082 kPa À1 (100-200 kPa) 0-200 kPa 6000 (10 kPa) [38] multiwalled carbon nanotubes (MWCNTs)/graphene (GR)/Fe 3 O 4 /silicone rubber (SR) 8.43 (0%-120% strain) 100.56 (120%-160% strain) 0.16-160% strain 9000 (10% strain) [39] PDMS/Ag 1.08 N À1 0-0.7 N 100 (0.7 N) [40] rGO/polyacrylic acid (PAA) 0.18 kPa À1 (0-1.5 kPa); 0.023 kPa À1 (3.5-6.5 kPa) 0-6.5 kPa 2000 (6.5 kPa) [41] Carbon black (CB)/polyurethane (PU) 0.068 kPa À1 (0-2.3 kPa); 0.023 kPa À1 (2.3-10 kPa); 0.036 kPa À1 (10-16 kPa); 0-16 kPa 50 000 (40% strain) [42] CuNWs/rGO/PDMS 0.144 kPa À1 0.1-15 kPa 1000 (15 kPa) [43] Polypyrrole (ppy)/rGO/fabric-sponge-fabric (FSF) 0.51 kPa À1 (0-1.5 kPa) 0.026 kPa À1 (1.5-8 kPa) 0.0015 kPa À1 (8-30 kPa) 0-30 kPa 7500 (1.5 kPa) [44] MXene/rGO 0.934 kPa À1 (0-0.6 kPa) 0.027 kPa À1 (0.6-7 kPa) 0.001 kPa À1 (7-50 kPa) 0-50 kPa 5000 (10 kPa) This work Bluetooth, the received signal can be displayed in real-time through the user interface designed using LabVIEW software.…”
Section: Applications Of the Tactile-sensing System In Multipoint Pre...mentioning
confidence: 99%
“…Monitoring human or robot activities is critically required in health care, artificial intelligence, industrial production, etc. Featured by simplicity in production and facileness in structure design, flexible piezoresistive pressure sensors have been extensively studied for the adaption of various testing conditions in the last 10 years. The key parameters for the sensing performance of pressure sensors mainly include sensitivity and effective pressure detection range. Meanwhile, a linear response is highly recommended for the convenience of data processing and delicate monitoring and controlling. Despite the significant improvements in sensitivity and effective pressure detection range, the linear response of pressure sensors is usually restricted in a limited range, which is hard to cover human motion pressure stimuli ranging from low- (0–10 kPa) to medium- (10–100 kPa) to high- (100–200 kPa) and further to ultra-high-pressure (>200 kPa) levels. For instance, a hybridized nanofibrous membrane-based pressure sensor and a multiscale hierarchical polyaniline/polyurethane pressure sensor have a linear response in ranges 0–50 and 0–160 kPa, respectively. , Although the construction of a microdome pattern could improve the linear response range of pressure sensors via stress concentration, it involves a complicated process in producing microdomes, thus limiting the commercialization of pressure sensors. , To that end, it is of great importance to develop a simple strategy to produce flexible pressure sensors with an excellent linear response in a wide detection range.…”
Section: Introductionmentioning
confidence: 99%